Sutureless Hemostatic Control During Laparoscopic NSS for the Treatment of Small Renal Masses. (February 2014) - Minervini, Andrea; Siena, Giampaolo; Tuccio, Agostino; Lapini, Alberto; Serni, Sergio; Carini, Marco
Background. This study aimed to evaluate the safety and efficacy of a sutureless hemostatic control during laparoscopic nephron sparing surgery (LNSS) for the treatment of small renal masses.Methods. Between November 2007 and August 2010, 245 patients underwent nephron sparing surgery. Overall, 100 patients (41%) had LNSS. Hemostasis was controlled either by a knot-tying suture repair (standard-LNSS) or by a sutureless technique (s-LNSS). The s-LNSS was done using a bipolar cauterization of the resection bed, followed by Floseal apposition. Operative and warm ischemia time (WIT), intraoperative blood loss, hospital stay, blood tests, and perioperative complications were recorded.Results. In 32 cases (32%) hemostasis was controlled by the sutureless technique. The s-LNSS was the treatment of choice for small tumors ≤1.5 cm, and it was also used for the treatment of tumors between 1.6 and 2.5 cm, aside from their spatial extension. Indeed, the mean (range; interquartile range) clinical dimension of the tumors in the s-LNSS group was 1.9 (1-3.5; 1.5-2.1) cm. On the contrary, the vast majority of tumors >2.5 cm were treated with standard-LNSS. Mean (range; interquartile range) WIT in the s-LNSS group was 16 (8-22; 12-16) minutes. The mean (range) intraoperative blood loss in the s-LNSS group was 107 cc (25-205). No postoperative early and late bleeding were reported in the s-LNSS group, and the mean (range) time to drainage removal and time to discharge were 3 (2-5) and 4 (3-7) days, respectively.Conclusions. The sutureless technique with bipolar cauterization of the surgical bed and Floseal apposition is safe and effective for the hemostatic control in the treatment of small cortical masses. It can be always used for tumors ≤1.5 cm and can be a valid option also for tumors between 1.6 and 2.5 cm, aside from their spatial extension.